2021
DOI: 10.1177/08971900211008625
|View full text |Cite
|
Sign up to set email alerts
|

Adherence, Persistence, and Effectiveness in Real Life. Multicenter Long-Term Study on the Use of Pirfenidone and Nintedanib in the Treatment of Idiopathic Pulmonary Fibrosis

Abstract: Background: In the treatment of idiopathic pulmonary fibrosis (IPF), nintedanib and pirfenidone, with their different mechanisms of action, lead to a reduction in the rate of progression of the fibrosis process measured by the reduction of functional decline, and, in particular, the decrease in forced vital capacity (FVC) and of the diffusion capacity of the lungs for carbon monoxide (DLCO). The objective of this study was to analyze real-life adherence, persistence and efficacy in the use of pirfenidone and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In fact, several doses per day are required, the medication has to be taken over a long period of time and there may be burdensome medication side-effects [8,9]. Prior studies primarily evaluated discontinuation rates (ranging between 21 and 58%) cross-sectionally or retrospectively, and used adherence measures, such as self-reporting or pharmacy refill data, which are known to underestimate adherence problems [10][11][12][13]. To investigate adherence to complex pharmacological regimens one needs accurate measurement methods.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several doses per day are required, the medication has to be taken over a long period of time and there may be burdensome medication side-effects [8,9]. Prior studies primarily evaluated discontinuation rates (ranging between 21 and 58%) cross-sectionally or retrospectively, and used adherence measures, such as self-reporting or pharmacy refill data, which are known to underestimate adherence problems [10][11][12][13]. To investigate adherence to complex pharmacological regimens one needs accurate measurement methods.…”
Section: Introductionmentioning
confidence: 99%
“…Our results should be interpreted with caution due to the declining numbers of patients over the course of the study. This is not uncommon in real-life and reflects the poor treatment persistence generally observed in IPF patients [34,35]. The strength of this study is represented by objective measurements of pulmonary function and the use of validated scores to assess severity of dyspnea [21], quality of life in chronic cough [20], and staging of IPF [19].…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only one study that examined the association between nintedanib adherence and outcomes. Santoleri et al reported a positive association between nintedanib adherence and FVC response one year after initiation among 144 nintedanib users in Italy during 2013–2019 [ 23 ]. Although a small number of studies examine the association of medication adherence and health and healthcare outcomes using the GBTM methodology, they vary greatly in their selected indications, outcomes and findings [ 30 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have documented nintedanib adherence in the United States using administrative claims data [ 20 22 ]. A small observational cohort study from Italy reported a positive association between levels of adherence to nintedanib and lung function response [ 23 ]. To date, however, no studies have examined the association between non-adherence to nintedanib and healthcare use and spending in patients with IPF.…”
Section: Introductionmentioning
confidence: 99%